Amebic Encephalitis in a Patient with Chronic Lymphocytic Leukemia on Ibrutinib Therapy - Ensi Voshtina; Huiya Huang; Renju Raj; Ehab Atallah (Case Reports in Hematology)
Chronic lymphocytic leukemia (CLL) is the most common type of leukemia in Western countries. A common first-line therapy offered to qualifying patients includes ibrutinib, an oral covalent inhibitor of Bruton’s tyrosine kinase. Treatment of CLL with ibrutinib therapy is generally well tolerated; however, serious opportunistic infections are being reported in patients treated with ibrutinib. In this report, we present a patient with CLL on ibrutinib therapy who developed rapidly declining neurological status concerning for the central nervous system (CNS) process related to his immunocompromised status. Despite multiple testing modalities, no evidence was found to explain the acute changes the patient was experiencing, and he had no improvement with common antimicrobial coverage. The patient ultimately expired, and autopsy of the brain revealed granulomatous amebic encephalitis due to opportunistic infection by Acanthamoeba species. As evidenced by this case, ibrutinib therapy, despite being generally well tolerated, has the potential to predispose patients to opportunistic infections like amebic encephalitis. Amebic encephalitis is a highly lethal CNS infection, and it is important for clinicians to recognize early on the potential for infection in patients on ibrutinib therapy presenting with CNS symptoms.